MEASUREMENTS OF CYTOPLASMIC PH IN INSULIN-RELEASING CELLS WITH INTRACELLULARLY TRAPPED PHENOL RED - Gylfe, E; Berggren, P; Rorsman, P (1986)
Cytoplasmic pH was measured in insulin-releasing clonal RINm5F cells using a new technique. The cells were permeabilized by electric discharges and loaded with phenol red. After resealing, changes in the absorbance of the intracellular indicator was monitored by dual wavelength spectrophotometry. The phenol red loading did not affect glucose metabolism, which was characterized by an oxidation to utilization ratio as low as 0.076. The basal cytoplasmic pH of the RINm5F cells was 7.25, and exposure to glucose caused intracellular acidification by 0.10 pH units. Since the RINm5F cells are characterized by a defective insulin response to glucose, the data do not support ideas that intracellular acidification is a link in the stimulus-secretion coupling of glucose-induced insulin release.